2012
DOI: 10.1177/0886260512468240
|View full text |Cite
|
Sign up to set email alerts
|

Initial Validation of the Spanish Childhood Trauma Questionnaire-Short Form

Abstract: The present study examines the internal consistency and factor structure of the Spanish version of the Childhood Trauma Questionnaire-Short Form (CTQ-SF) and the association between the CTQ-SF subscales and parenting style. Cronbach's α and confirmatory factor analyses (CFA) were performed in a female clinical sample (n = 185). Kendall's ι correlations were calculated between the maltreatment and parenting scales in a subsample of 109 patients. The Spanish CTQ-SF showed adequate psychometric properties and a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 45 publications
5
78
0
6
Order By: Relevance
“…Twenty-five items relate to experiencing childhood abuse and indicate the severity of the experience, while three items assess for denial/underreporting. Previous research has demonstrated that the CTQ-SF has good reliability and validity (Bernstein et al, 2003; Hernandez et al, 2012; Thombs, Bernstein, Lobbestael, & Arntz, 2009). In the current study, we administered the Italian CTQ-SF (Sacchi, Vieno, Simonelli, 2017), in which the original five-factor structure is confirmed and the Cronbach’s alpha ranges across subscales between .87 and .96.…”
Section: Methodsmentioning
confidence: 97%
“…Twenty-five items relate to experiencing childhood abuse and indicate the severity of the experience, while three items assess for denial/underreporting. Previous research has demonstrated that the CTQ-SF has good reliability and validity (Bernstein et al, 2003; Hernandez et al, 2012; Thombs, Bernstein, Lobbestael, & Arntz, 2009). In the current study, we administered the Italian CTQ-SF (Sacchi, Vieno, Simonelli, 2017), in which the original five-factor structure is confirmed and the Cronbach’s alpha ranges across subscales between .87 and .96.…”
Section: Methodsmentioning
confidence: 97%
“…CTQ subscales scores were related to severity, frequency, and duration of maltreatment (Fink, Bernstein, Handelsman, Foote, & Lovejoy, 1995). The Spanish CTQ version showed internal consistency coefficients similar to the original version (average α = .83), and the confirmatory factor analyses replicated the original five-factor structure (Hernández et al, 2012). The sample analyzed for the Spanish CTQ validation included data from patients in the present study.…”
Section: Structured Clinical Interview For Dsm-iv Axis II Personalitymentioning
confidence: 82%
“…Ambos os estudos confir maram a estrutura de cinco fatores, e identificaram a subescala de negligência física como tendo baixa consistência interna. Em Espanha, a estrutura fatorial do CTQ-SF foi também estudada, tendo-se confir mado o modelo de cinco fatores numa amostra clínica de 189 mulheres, com valores de consistência interna a variar entre .84 para a negligência emocional e .94 para o abuso sexual, e .66 para a negligência física (Hernandez et al, 2012). No entanto, Villano et al (2004) verificaram uma adequação pobre do modelo dos cinco fatores quando estudou um grupo de jovens mulheres que se dedicavam à prostituição de rua.…”
Section: Amostraunclassified
“…O Questionário de Trauma de Infância (CTQ-SF) é um dos instrumentos mais usados internacionalmente no estudo do maltrato infantil em adolescentes e adultos (Baker & Maiorino, 2010;Roy & Perry, 2004;Thombs, Bernstein, Lobbestael, & Arntz, 2009), e que integra as considerações sugeridas por Gerdner e Allgulander (2009) (Hernandez et al, 2012). Numa revisão de literatura acerca de instrumentos de avaliação de maltrato durante a infância, Strand, Sarmiento e Pasquale (2005) classificaram o CTQ-SF como um instrumento breve, de uso fácil e que apresenta boas características psicométricas, nomeadamente boa consistência interna, boa fiabilidade teste-reteste e estrutura interna robusta.…”
Section: Introductionunclassified